Analisis Kualitas Pelayanan Penyedia Jasa GO-JEK dan Dampaknya terhadap Masyarakat - Irgi Saeful Rizky; Ili Luhung; Andika Alexandro (Universitas 45 Surabaya, 2025)
In today's rapidly advancing digital era, technological progress has significantly transformed various aspects of life within society. This shift has led people to prefer communication through social media and influenced transportation tools connected to digital platforms. Communication and transportation are directly related to societal activities. These two aspects are frequently utilized by individuals to simplify their tasks. Moreover, with the increasing sophistication of technology in the fields of transportation and communication, society has become increasingly dependent on these aspects. This phenomenon is a result of rapid technological advancements across various sectors, including communication and transportation. The development of technology in these areas has encouraged people to be more creative and innovative in leveraging these advancements to start new businesses, particularly those providing transportation services.